PENGARUH QUALITY OF WORK LIFE (QWL) TERHADAP PRODUKTIVITAS KERJA DI THE SANCHAYA BINTAN - Helma Pionistika; Feri Ferdian (Ensiklopedia Education Review, 2023)
The background of this research is the discovery of problems related to quality of work life and work productivity at The Sanchaya Bintan. The purpose of this research is to analyze the effect of quality of work life on employee work productivity. The type of research used in this research is quantitative with a causal associative approach. The data used in this study are primary and secondary data. The population of this research is the employees of The Sanchaya Bintan. The research sample was 100 respondents using the non-probability sampling method and the type of non-probability sampling used was saturated sampling. Data collection techniques were carried out using a questionnaire (questionnaire), whose validity and reliability were tested with a Likert scale. The data for this study were processed using SPSS 22.00. The results of this study indicate that the quality of work life is in the fairly good category at 67.7%. In addition, the work productivity variable is in the fairly good category at 68.1%. The effect of quality of work life (X) and work productivity (Y) obtained an R square value of 0.259, meaning that the effect of quality of work life on work productivity is 25.9%. In addition, the results of simple linear regression analysis produce a calculated F value of 34,215 sig. 0.000 <0.05, meaning that the variable quality of work life has a significant effect on work productivity, and the t value is 5,849 with sig. 0.000 < 0.05.Keywords: Quality of Work Life, Work Productivity, Employee, Hotel